GROUP A BETA HEMOLYTIC STREPTOCOCCAL CARRIAGE AND ANTIBIOTIC SENSITIVITY AMONG SCHOOL GOING CHILDREN IN MARDAN, PAKISTAN - Akram, Sumera; Khan, Muhammad Ahmed; Khan, Saeed Akhtar; Usman Shah, Hassan Bin (Journal of Postgraduate Medical Institute, 2021)
Objective: To assess the carriage rate of Group A beta hemolytic streptococci (Streptococcus Pyogenes/ GABHS) among school children and find out their antibiotic sensitivity. Methodology: This cross-sectional study was carried out on 200 healthy children residing in Mardan, while samples were processed at Department of Pathology, Combined Military Hospital (CMH) Mardan from June 2019 to September 2019. Asymptomatic children with age range from 5 to 15 years were enrolled in this study. After informed consent, throat swabs were taken under aseptic conditions and sent to laboratory for culture and sensitivity. The GABHS were identified by beta-hemolysis, colony morphology, gram staining, catalase reaction and sensitivity to bacitracin. Antibiotic susceptibility of beta hemolytic streptococci were found for Penicillin G, Ceftriaxone, Erthromycin, Co-amoxiclav, Ceftriaxone, Vancomycin, Azithromycin, Tetracycline and Cephalexin by Kirby disc diffusion method. SPSS v.20.0 was used as statistical tool. Results: Out of 200 children, there were 97 (48.5%) male. The mean age was 9.71± 2.95 years. A total of 23 (11.5%) cultures were positive for GABHS. Among these 23 carriers, 10 were males and 13 were females. All were found sensitive to Vancomycin, Penicillin G and Azithromycin. Isolates were 95.6% sensitive to Clindamycin, Ceftriaxone and Co-amoxiclav (n=22). Sensitivity to Cephalexin, Erythromycin and Tetracycline were 78.3% (n=18), 69.5% (n=16) and 65.2% (n=15), respectively. Conclusion: GABHS carriage is common among asymptomatic school going children. GABHS cultured from these children are highly sensitive to Penicillin G, Vancomycin, Azithromycin, Co-amoxiclav, Clindamycin and Ceftriaxone.